THE PLACE AND ROLE OF TECHNICAL TOOLS IN FOREIGN LANGUAGE TEACHING. - Buriev Dilmurod Arzimurodovich; Sattorov Jumanazar O`tkir ugli (Ta'lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT: to provide insights and recommendations to future foreign language teachers in improving their professional skills, the importance of modern multimedia tools and the pedagogical and psychological basis of their use, multimedia, which is currently serving as a priority direction of modern education in the educational system aimed at teaching a foreign language with the help of technologies and introducing scientific information and new ways of methodical organization of a foreign language lesson with the help of technical tools during the lesson.